1984
DOI: 10.1079/bjn19840006
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in the antigenicity of whey proteins by heat treatment: a possible strategy for producing a hypoallergenic infant milk formula

Abstract: Residual antigenic protein in heat-denatured cow's milk whey and in two commercial infant milk formulas was determined using enzyme-linked immunosorbent assays specific for beta-lactoglobulin, alpha-lactalbumin, bovine serum albumin, bovine IgG1 and alpha-casein. This immunochemical assessment of antigenicity was related to the capacity of the preparations to sensitize immunologically when fed to guinea-pigs for 2 weeks. Antibody production was measured and the susceptibility of the animals to systemic anaphyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
1

Year Published

1985
1985
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(22 citation statements)
references
References 11 publications
2
19
1
Order By: Relevance
“…The binding between IgEs and these proteins was not affected by heat treatment, contrary to what had been reported previously for the group of cow's whey proteins, which included BSA [15, 16]. The responses to all native serum albumins was maintained after heating, apart from the IgE of child 2, which did not recognize heated PSA.…”
Section: Discussioncontrasting
confidence: 51%
See 2 more Smart Citations
“…The binding between IgEs and these proteins was not affected by heat treatment, contrary to what had been reported previously for the group of cow's whey proteins, which included BSA [15, 16]. The responses to all native serum albumins was maintained after heating, apart from the IgE of child 2, which did not recognize heated PSA.…”
Section: Discussioncontrasting
confidence: 51%
“…Although data on the reduction of antigenicity of total whey proteins after heating is reported in in vitro and animal models [16, 17, 18], little is known about the antigenicity of heated BSA in humans. Moreover, it would be interesting to investigate the binding between human IgEs and serum albumins after different structural modifications, since these data could supply new information on IgE–mediated reactions associated with BSA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have recently shown that chemical or heat denaturation of ovalbumin (OVA) can abrogate the induction of oral tolerance in mice [8, 9, 10]. Whereas some reports revealed that piglets and calves fed heated soybean proteins developed severe intestinal hypersensitivity and antibody responses [11, 12], other reports showed that heat treatment of cow's milk could minimize oral anaphylactic sensitization in guinea pigs [13, 14, 15, 16]. Such discrepancies may be due to different species of experimental animals.…”
Section: Introductionmentioning
confidence: 99%
“…Pep sin associated with trypsin or chymotrypsin hydrolysis constitutes an efficient combination of enzymes to reduce in vitro allergenicity of oe-lactalbumin and~-lactoglobulin (Pahud et al, 1985;Asselin et al, 1988Asselin et al, , 1989. Heat treatment of whey proteins has been shown to reduce antigenicity, but has been associated with a loss of available lysine (Heppell et al, 1984;Jost et al, 1987). According to Jost et al (1987), combining selective hydrolysis by specifie proteases with processing or subsequent heat treatments appeared to be a promising approach in developing a hypoallergenic infant formula.…”
Section: Introductionmentioning
confidence: 99%